Pengelolaan Kelas dalam Menciptakan Lingkungan Pembelajaran yang Positif - Habsy, Bakhrudin All; Eraeni, St.; Rahmadania, Aulia Nur; Rahmadhani, Rizky (TSAQOFAH, 2024)
Learning is a conscious and planned effort to create a learning atmosphere and educational process so that students actively improve their abilities, so that the educational process should be able to produce a classroom atmosphere that is conducive to supporting the creation of a quality educational process. The methodology used to create this article is to use literature review procedures. Researchers use this method because researchers want to understand and master classroom management in producing positive educational areas using a literature research approach. grouping of students according to their development, which, among other things, is based on their respective chronological boundaries. A class in a broad sense is a small community which is part of a school community which is organized into a work unit that dynamically carries out creative teaching and educational activities for a purpose. Based on the results of literature research, it can be concluded that learning is a planned effort to realize the educational process so that students can actively improve their abilities, and teachers have an obligation to realize the dreams and goals of learning. A conducive educational process makes students more active, motivated and at home in learning.